The manufacture of fixed dose combination products using advanced pharmaceutical techniques for the treatment of cardiovascular disease and type II diabetes - KELLEHER, JEREMIAH FRANCIS (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2020)
The thesis has focused on the use of continuous manufacturing techniques to produce fixed dose combination (FDC) products for the treatment of type II diabetes mellitus and cardiovascular diseases (CVDs). FDC products with monophasic and biphasic release profiles of the active pharmaceutical ingredients (APIs) were successfully manufactured via spray drying (SD), hot melt extrusion (HME), melt granulation (MG) and spray coating (SC). The impact of manufacturing technique on the products was studied, as well as the role excipients and their molecular makeup have on the final product characteristics. Monolithic FDC products of hydrochlorothiazide (HCTZ) and ramipril (RAM), with an immediate release (IR) profile, were manufactured via HME and SD and the resulting physicochemical characteristics analysed and compared with one another. The work highlighted the role manufacturing techniques play on the final product characteristics and how, with the addition of appropriate plasticizers, thermal degradation in the HME process can be overcome. Monolithic FDC products of metformin hydrochloride (MET) and sitagliptin phosphate (SIT), with an IR profile, were manufactured via MG and SD. The influence manufacturing technique as well as the chosen HPC polymer composition were analysed and studied for their influence on the final product characteristics. Due to the large dosage size of MET, the quantities of excipients used for processing had to be kept to a minimum. Two HPC polymers were chosen for the formulations which varied in molecular weight and degree of hydroxypropoxy substitution. The work highlighted, as with the HCTZ and RAM study, the role manufacturing technique plays on the final product characteristics as well as the influence polymer composition has on the final product also. MG may be seen as a better alternative than SD for manufacturing large API dose products due to no solvents being required, products having better flow properties and, being seen as a continuous process as the end product can be fed directly into the next phase of processing. A HME ? heat aided spheronisation ? SC technique was successfully trialed to produce biphasic release FDC products as an alternative to hot melt co-extrusion (HMCE). Firstly, a delayed release formulation of simvastatin (SIM) was successfully manufactured via HME followed by a heat aided spheronisation phase to produce spherical pellets. This was followed with SC via a fluid bed dryer (FBD), of an IR formulation of HCTZ and RAM to create a novel FDC product for the treatment of CVDs. Secondly, a sustained released formulation of the thermolabile API, gliclazide (GLZ), was successfully manufactured via HME followed by a heat aided spheronisation phase to produce spherical pellets. This was followed with SC via a FBD of an IR formulation of SIT to produce a novel FDC product for the treatment of type II diabetes. The work conducted and presented in this thesis highlights the many modern continuous methods of manufacturing that can be applicable for FDC product production. Solvent free methods such as MG and HME may be more favourable due to being seen as a ?greener? technology that is better for the environment due to no harsh solvents being used. While thermolabile API manufacturing via MG and HME may be difficult, the work in this thesis has shown with the correct excipients and conditions chosen, product manufacture via these methods is possible. While solvent methods such as SD and SC may be seen as less favourable production techniques, they still have a vital role in developing formulations with desirable characteristics and release profiles.
APPROVED
Keywords: Continuous Manufacturing; Fixed Dose Combination; Hot Melt Extrusion; Spray Coating; Spray Drying; Diabetes; Cardiovascular Disease